2022
DOI: 10.1101/2021.12.31.474652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expectation violations produce error signals in mouse V1

Abstract: Repeated exposure to visual sequences changes the form of evoked activity in the primary visual cortex (V1). Predictive coding theory provides a potential explanation for this, namely that plasticity shapes cortical circuits to encode spatiotemporal predictions and that subsequent responses are modulated by the degree to which actual inputs match these expectations. Here we use a recently developed statistical modeling technique called Model-Based Targeted Dimensionality Reduction (MbTDR) to study visually-evo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…This result could reflect the fact that local field potentials largely represent synaptic currents in the dendrites (e.g., inputs) rather than neural spiking (e.g., outputs, Katzner et al, 2009 ). In more recent experiments in our lab, we have found that expectation-violating stimuli tend to elicit more spiking activity ( Price et al, 2022 ). In addition to this unsupervised learning paradigm, there is also evidence for timing information in V1 following reinforcement learning ( Shuler and Bear, 2006 ; Hangya and Kepecs, 2015 ; Levy et al, 2017 ).…”
Section: Efficient Coding In Primary Visual Cortexmentioning
confidence: 88%
“…This result could reflect the fact that local field potentials largely represent synaptic currents in the dendrites (e.g., inputs) rather than neural spiking (e.g., outputs, Katzner et al, 2009 ). In more recent experiments in our lab, we have found that expectation-violating stimuli tend to elicit more spiking activity ( Price et al, 2022 ). In addition to this unsupervised learning paradigm, there is also evidence for timing information in V1 following reinforcement learning ( Shuler and Bear, 2006 ; Hangya and Kepecs, 2015 ; Levy et al, 2017 ).…”
Section: Efficient Coding In Primary Visual Cortexmentioning
confidence: 88%
“…The internal model could serve as the knowledge of familiarity, and their inhibitory influence on familiar stimulus responsiveness may contribute to novelty detection. Consistently, deviation from or memory of expected sensory experience has been shown to modulate neuronal activity in the visual cortex 30,38,59,[62][63][64][65][66][67][68][69] .…”
Section: Discussionmentioning
confidence: 99%
“…To separate these two effects, subsequent experiments went beyond the oddball paradigm and employed stimuli that become predictable only given a wider context. These experiments showed that also without stimulus adaptation neurons can show strong prediction mismatch responses (PMRs) [6, 7, 8, 9, 10, 11, 12]. While it is still a matter of ongoing research how exactly PMRs arise, they often seem to be modulated by top-down inputs to the cortical circuits [4, 13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%